(untitled) (Bangladesh Critical Care Journal, 2015)
Background: Microbial resistance to antibiotics is nowadays a great threat to intensive care unit patients especially in severe pneumonia leading to high morbidity and mortality. Bacterial profile and antibiotic sensitivity pattern would help clinician in selecting more proper empirical therapy before isolation of microbes. Materials and Methods: This retrospective study was performed among 210 patients of lower respiratory tract infection in intensive care unit in Square Hospitals Ltd, a tertiary care hospital in Dhaka. Sputum, tracheal aspirates or broncho alveolar lavage were cultured, identified and antibiotic sensitivity pattern performed by standard methods. Results: Of 210 specimens, 150 (71%) were culture positive and 60 (29%) showed no growth. From 150 culture positives, 216 isolates were recovered, of which 7 specimen shows more than 2 organisms each, 52 specimen shows 2 isolates per specimen remaining 91 specimen with single isolates were recovered. The most common organisms in order of frequency were, Acinetobacter baumannii (24.0%), Staphylococcus aureus (20.6%), Klebsiella pneumoniae (19.3%), Pseudomonas aeruginisa (19.3%), Escherichia coli (14%) and Candida albicans (13%). A very high rate (83-93%) of resistance was observed among Acinetobactor baumanni to Beta lactum and clavulanate, Cephalosporin, Quinolones and Carbapenem. No resistant was observed with Colistin. Linezolid and Vancomycin are most effective against methicillin resistant Staphylococcus aureus, Coagulase negative Staphylococcus aureus and Escherichia coli, where no resistance was found. Conclusion: Farmenter and nonfermenters are the both common etiological agents of lower respiratory tract infections in this intensive care unit. There is high rate of resistance to commonly used cephalosporin and ?-lactam-?-lactamase inhibitors and quinolone group of drugs. Acinetobacter baumannii, Pseudomonas aeruginisa and Klebsiella showed most sensitivity to Colistin and actually no resistance was found. Bangladesh Crit Care J September 2014; 2 (2): 53-56